Branchial Chamber and Gastrointestinal Tracts Parasites of Fish Species in Benue and Niger Rivers, North Central, Nigeria. (5th March 2021) - Onoja-Abutu, Agatha Eleojo; Okpanachi, Martin Abdubala; Alkazmi, Luay; Yaro, Clement Ameh; Batiha, Gaber El-Saber
Abstract : Freshwater fish species are posing health challenges by either serving as host of parasites that are harmful to man and animals. This study was conducted to determine the parasitic profile of the branchial and gastrointestinal tracts of freshwater fish species from Niger and Benue rivers at Lokoja. These fish species are Tilapia zillii, Oreochromis niloticus, Clarias species, Synodontis schall, and Megalops atlanticus . Fish samples were collected within a period of 12 months, and the species and sex of the fish were identified. The two opercula of each fish were removed and examined for parasites; parasites recovered were preserved in 0.7% physiological saline. Gastrointestinal tracts were removed from each fish, placed in physiological saline, and examined microscopically for parasites. Prevalence of parasites was calculated. The chi-square test was used to compare prevalence of parasites according to sexes, body parts examined, fish species, and parasites species, while the t -test was used to compare between gills and intestines of each fish species. The chi-square test was used to determine if any significant difference exists in prevalence between the sexes, body parts, fish species, and parasites species, while the t -test was used to determine if any significant difference exists in prevalence between the gills and intestines of each fish species. A total of seven parasites species were harboured in branchial chamber and gastrointestinal tracts of fish species from rivers Niger and Benue: Clinostomum sp. (trematode), Camallanus sp. (nematode), Capillaria sp., Rhabdochona congolensis (nematode), Contracaecum sp. (nematode), Proteocephalus sp. (cestode), and Spinitectus guntheri . T. zillii (81 (95.3%)) had the highest prevalence, while O. niloticus, Clarias sp., S. schall, and M. atlanticus had prevalence of 87 (89.7%), 96 (80.0%), 48 (70.6%), and 27 (38.6%), respectively. Out of the total fish samples examined, females (191 (80.3%)) were observed to harbour more parasites than males (148 (73.3%)). The gastrointestinal tracts (287 (65.2%)) significantly harboured more parasites than branchial chamber (52 (11.8%)). Fish species in rivers Niger and Benue are highly infected with parasites. Fish consumers should subject the fish to proper processing before consumption, as some of these parasites are of zoonotic importance.